As vidas possíveis das alianças entre os ouriços-do-mar e os seres humanos: Estudo comparativo da Festa da Ouriçada na Baía de Suape (Pernambuco, Brasil) e da Fête de l'Oursinade de Carry-le-Rouet (Bouches-du-Rhône, França) - Santos, Juana de Oliveira (2021)
Contemporary society tends to experience and perceive the relationship between culture and nature through a dualistic and paradoxical perspective, but a deeper analysis reveals nuances that escape the dichotomous worldview, especially when we observe phenomena of festive effervescence. Thus, this research investigates these nuances of the culture-nature relationship materialized in two distinct festivities — the Sea Urchin Festivals in Suape Bay (Pernambuco, Brazil) and Carry-Le-Rouet (Bouches-Du-Rhône, France) — which present great asymmetries between them. These two festivities are considered cultural expressions devoted to the celebration of the marine environment and they have the sea urchin as its protagonist. The research is based on an ethnographic study with a comparative perspective and bibliographical research aiming to explore interdisciplinary concepts and approaches observed in these festivities. These festivities are originating in two distinct communities, but they are historical and traditionally linked to artisanal fishing. They oscillate, in their way, in the dichotomous pendulum of their potential and threats with nature, sometimes being a factor of preservation, sometimes of environmental impact. By crossing physical or symbolic borders, this study sought to highlight the multiplicity of the world, the intercultural and interdisciplinary connections in the unlikely encounter of these festivities dedicated to commensality. This research considers that festivities are a conscious or unconscious response to the impulse — both natural and social — inherent to human beings to forge relational ties between themselves and with the world around them, and to this end, humanity continues to create and recreating practices and rituals like these two festivities. This research concluded that, as an object of desire, the sea urchin is highlighted as the principal common point between these two festivals. However, sea urchin is the cardinal point to establish the phenomenon of sociability among commensals, showing the directions for the relationship between culture and nature. It is from the sea urchin that radiates — as radiates the thorns of its skin — the various possibilities of encounters, as well as radiates the threads through which the lives of the Sea Urchin Festivals flow.